Optimalisasi Biaya Transportasi Produk UMKM Rambak Kulit Sapi Di Kampung Rambak Klaten - Yuliana, Yuliana; Agnia Dinda Arisandi; Lala Areta Prameswari; Kintan Maharani Zahra (Pendidikan Matematika Universitas PGRI Yogyakarta, 2025)
One of the famous micro, small, and medium enterprises (UMKM) in Cawas, Klaten, Central Java, is cowhide rambak. Its existence has been around for a long time until now. In fact, this place is known as the Rambak village. Cowhide Rambak is one of the UMKM rambaks that continues to grow. This UMKM faces problems with optimizing the distribution costs of its products. Cowhide rambak sends its products to three distributors in Klaten, Sukoharjo, and Yogyakarta and offline, with a monthly transportation cost of IDR 879,000.00. The management of this cowhide rambak UMKM has not been able to reduce shipping costs due to limited human resources. This study will find the optimum shipping costs for rambak UMKM products in the Cawas Rambak Village. Data collection was carried out by interviewing UMKM owners, observing production activities, and documenting sales activities and shipping of UMKM products. The data that has been collected is then analyzed using transportation cost optimization with the Vogel approach. The shipping cost of the product before using the Vogel approach method is Rp879,000.00, while the transportation cost of shipping the product using the Vogel approach is Rp832,000.00. Cowhide rambak UMKM is able to save Rp47,000.00 per month. KEYWORDS: Optimization, UMKM Rambak, Vogel